2019
DOI: 10.1097/dbp.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Both Child Behavior and Social Determinants of Health in Pediatric Primary Care

Abstract: Objective-To implement comprehensive screening for child behavior and social determinants of health in an urban pediatric practice, and explore rates of referrals, and follow-up for positive screens.Method-Quality improvement (QI) methodology was used to implement routine screening using an adapted version of the Survey of Well Being of Young Children (SWYC), a child behavior and social screen, for all children ages 6 months to 10 years. Rates of screen administration and documentation were assessed for 18 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). 33-90 Fifty-eight studies were conducted with primary care patients, 29-31,33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). 33-90 Fifty-eight studies were conducted with primary care patients, 29-31,33…”
Section: Resultsmentioning
confidence: 99%
“…The remainder reported using observational study designs (eg, pre-post studies, feasibility studies, pilot studies). Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…North American publications using the SWYC scale report prevalence rates ranging from 28 to 47% for suspected cases of changes in social-emotional development. 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%